REFORMA PEMERINTAH KOTA SAMARINDA MELALUI PROGRAM "KOTAKU" DALAM PENYELESAIAN SENGKETA BANTARAN SUNGAI KARANG MUMUS - M. Gilang Akbar Ramadhan; Ahwil; Anggit Dwi Hasti Oenawan; Saydati Hastuti (Journal of Policy & Bureaucracy Management, 2020)
The implementation of agrarian reform certainly faces obstacles. One of the problems faced is agrarian disputes. Arrangement of land use, ownership, and utilization is based on the development design in the form of habitable settlements for the people of Samarinda City. The purpose of this study is to find out what are the problems of agrarian disputes and how the agrarian reform carried out by the Samarinda City Government in resolving agrarian disputes that exist on the banks of the Karang Mumus River in Dadi Mulya Village, Samarinda City. Through the government policy contained in the issuance of the "KOTAKU" (City Without Slum) Program, it is hoped that it can prevent, deal with, and reduce the number of slum areas on the banks of the Karang Mumus River by means of a humane approach in resolving agrarian disputes and empowering physically and non-physically in the area.